A Review on the Experimental Study of Cold-Formed Steel Columns with Holes subjected to an Axial Load - Dang, Elvida Runai; Jamaluddin, Norwati (Recent Trends in Civil Engineering and Built Environment, 2021)
This paper represent a review of experimental work study with the aim to determine and evaluate the reaction that occurs on CFS columns that are perforated and non-perforated when subjected to axial load. The use of CFS in construction is getting popular and widely used. The CFS members commonly has complex buckling behaviour and buckling mod. Slenderness is the main factor that affects the stability and buckling failure in CFS. This paper reviewed experimental works on CFS columns from past studied to assess the responds of the column in affect the buckling mod and mode of failure. The CFS columns of closed type cross section column with and without perforated are chosen and carried out in this study. A compression test was used to determine the effect of a column reaction under compression load. The tests performed with various parameters such as the slenderness, thickness, temperature and hole in the column web. Based on the results of experimental works found that the perforated RHS column as thin as 1.25 mm failed due to local buckling. Through this study, holes have influences on behaviour of the column buckling. The hole size is the factor affects the behavior of column, as well as the temperature such as high temperature affect the buckling mode. From the slenderness point of view, hort column tend to experience local buckling, while slender column tends to experience global buckling. In addition, column filled with concrete and steel bars affect the value of the ultimate load and local buckling load as the concrete infill provides support to the CFS column and slow down the bucking process from occurring. Therefore, various effects can be seen from this study.